2016
DOI: 10.1111/conl.12320
|View full text |Cite
|
Sign up to set email alerts
|

Status and Trends in Global Ecosystem Services and Natural Capital: Assessing Progress Toward Aichi Biodiversity Target 14

Abstract: The Convention on Biological Diversity uses six indicators to assess progress toward Aichi Biodiversity Target 14 (ecosystem services), leaving many elements of the target untracked. We identify 13 ecosystem services as directly essential for human well-being, and select a set of 21 datasets as indicators of the state of natural capital underpinning those services, the benefits derived from them, and distribution of access to those benefits. Analysis of these indicators supports previous conclusions that there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…Each ‘Aichi Target’ was designed to better understand and predict biodiversity dynamics, such as how biological diversity underpins ecosystem function, and how the provision of ecosystem services is essential for human well-being. Meeting the Aichi Targets would ultimately benefit local livelihoods and economic development, and is essential for biodiversity maintenance and poverty reduction (Shepherd et al, 2016; Tittensor et al, 2010). In this paper, we report on the findings of a working group that discussed how the targets related to marine biodiversity were being achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Each ‘Aichi Target’ was designed to better understand and predict biodiversity dynamics, such as how biological diversity underpins ecosystem function, and how the provision of ecosystem services is essential for human well-being. Meeting the Aichi Targets would ultimately benefit local livelihoods and economic development, and is essential for biodiversity maintenance and poverty reduction (Shepherd et al, 2016; Tittensor et al, 2010). In this paper, we report on the findings of a working group that discussed how the targets related to marine biodiversity were being achieved.…”
Section: Introductionmentioning
confidence: 99%
“…However, the set of indicators used for target monitoring is sometimes inadequate, hindering the ability to accurately monitor some of the targets (Shepherd et al . ). More alarmingly, there is evidence that different indicators can lead to contrasting assessments.…”
Section: Defining Efficient Conservation Strategiesmentioning
confidence: 97%
“…An important part of an efficient global plan for biodiversity conservation is the establishment of an efficient framework for monitoring progress toward targets. However, the set of indicators used for target monitoring is sometimes inadequate, hindering the ability to accurately monitor some of the targets (Shepherd et al 2016). More alarmingly, there is evidence that different indicators can lead to contrasting assessments.…”
Section: Defining Efficient Conservation Strategiesmentioning
confidence: 99%
“…In short, the status of most of the planet's ecosystems is declining (Shepherd et al 2016;IPBES 2019) and species continue to be lost at a pace 1000 times the background rate (De Vos et al 2015). The growing problems posed by habitat change, overexploitation of natural resources, habitat fragmentation, spread of invasive alien species, and changing climate have shown that more effective approaches to sustainable resource management are required.…”
Section: But Protected Areas Are Facing Major Challengesmentioning
confidence: 99%